Pendampingan Pemograman Kartu Rencana Studi (KRS) Online Bagi Mahasiswa Di Lingkungan STKIP PGRI Situbondo: Pengabdian - Yesi Puspitasari; Rahmat Shofan Razaki; Cholifia Seasilina Efendi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Filling out the Study Plan Card (KRS) is a crucial part of the academic system at STKIP PGRI Situbondo. The current online KRS programming system still uses the SIAKAD system. Therefore, the increasing number of students makes the campus' system highly efficient in terms of both time and cost. The online KRS system at SIAKAD at STKIP PGRI Situbondo aims to replace the manual KRS system, ensuring smooth student learning and significantly assisting lecturers in the three study programs at STKIP PGRI Situbondo. The results of the online KRS programming assistance for students, assisted by PDDIKTI Operators in the academic division, demonstrate that with the implementation of the new SIAKAD system, combined with web-based and mobile online KRS programming applications at STKIP PGRI Situbondo, the KRS filling process has become more practical and efficient in terms of both time and cost. Students can complete their KRS anywhere, as long as they are aware of the curriculum they are taking in their semester.